Readiness of Elementary School Teachers in Implementing Online Learning and "Merdeka Belajar" During Covid-19 Pandemic - Rini Kristiantari (Jurnal Ilmiah Sekolah Dasar, 2021)
As a result of the COVID-19 pandemic, the government issued a policy to change learning and teaching activities offline to online. However, there are still many obstacles experienced by teachers and students in implementing online learning. The purpose of this study is to analyze and evaluate the level of readiness of elementary school teachers, especially low-grade teachers, in dealing with and implementing online learning and independent learning during the covid-19 pandemic. This research belongs to the type of evaluative research (evaluation study). The research data is in the form of verbal attitude statements from the subjects studied, namely elementary school teachers in low or early grades. Data were collected using questionnaires and interviews. The data that has been collected is then analyzed descriptively qualitatively. The results of the analysis of document study data and interviews showed that 70% of lower grade elementary school teachers as the research subjects tended to state that they were ready to carry out online learning and were free to learn for their students. This readiness is coupled with the expectation of the availability of online learning facilities for both teachers and students and training on the use of IT media for teachers to create smooth and innovative online learning. The implication is that even though learning is carried out online by adhering to independent learning according to existing provisions, the process and student learning outcomes will be maintained and carried out properly according to the expectations, which are also stated in the learning objectives.